2007
DOI: 10.1631/jzus.2007.b0338
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of fruit shape traits at different maturation stages in sponge gourd

Abstract: Abstract:The fruit shape is important quantitative trait closely related to the fruit quality. However, the genetic model of fruit shapes has not been proposed. Therefore, in the present study, analysis of genetic effects for fruit shape traits (fruit length and fruit perimeter) in sponge gourd was conducted by employing a developmental genetic model including fruit direct effects and maternal effects. Analysis approaches of unconditional and conditional variances were applied to evaluate the genetic behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…Genetic analysis of fruit shape traits at different maturation stages in sponge gourd was evaluated (S. H. J. Zhang et al, 2007) and it was found that it was relatively easy to improve fruit shape traits by carefully selecting the parents at economic maturation stage than the physiological maturation stage. Developmental genetic analysis of fruit shape traits in sponge gourd.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis of fruit shape traits at different maturation stages in sponge gourd was evaluated (S. H. J. Zhang et al, 2007) and it was found that it was relatively easy to improve fruit shape traits by carefully selecting the parents at economic maturation stage than the physiological maturation stage. Developmental genetic analysis of fruit shape traits in sponge gourd.…”
Section: Resultsmentioning
confidence: 99%
“…The results of variance analysis indicated that fruit length and fruit circumference were simultaneously affected by fruit direct genetic effects and maternal effects. Fruit direct genetic effects were relatively more important for fruit shape traits than fruit weight during whole developmental period (Beyer et al, 2002;Wu et al 2006;S.H.J. Zhang et al, 2007).…”
mentioning
confidence: 99%
“…The differences between the two training systems could affect the nutritional and sensory quality of the fruits, because of the interlink between the phytochemical composition and photosynthetic process Other factors such as a fertilization of the soil, temperature, atmospheric humidity and rainfall could contribute to the sensory and phytochemical quality of the fruits due to their effect to modulate the secondary metabolites pathways . Data regarding this effect on the sensory profile of fruits are rather scarce and the findings from the few reports are often limited to evaluate traditional/organic systems or sunlight influences on fruit shape or size …”
Section: Introductionmentioning
confidence: 99%
“…Fruit shape (length and width) of yellowhorn is reported to be highly correlated with fruit yield (Chai et al 2013) and as in many species [e.g., Douglas-fir (El-Kassaby and Cook 1994); apple (Stajnko et al 2009); pear (Canli and Pektas 2015)] is under strong Communicated by P. Ingvarsson genetic control [i.e., high heritability (El-Kassaby 1995;Grandillo et al 1999;Serquen et al 1997;Tan et al 2015)]. The observed high heritability for fruit shape in other species is attributable to the presence of major genes (Cantín et al 2010) and strong maternal effect (Zhang et al 2007). In spite of the reported fruit shape's high heritability, the breeding system and/or its mode of inheritance of yellowhorn have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Hand-pollination experiment is one way to determine a species' breeding system and differences among its biological characteristics such as fruit shapes (Zhang et al 2007). We are aiming at addressing three principal questions: (1) Does fruit shape allow to infer yield potential?…”
Section: Introductionmentioning
confidence: 99%